2014
DOI: 10.1007/s10266-014-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of locally delivered gel containing green tea extract as an adjunct to non-surgical periodontal treatment

Abstract: MU-IRB 2008/153.0511, ClinicalTrials.gov NCT00918060).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
0
17
0
3
Order By: Relevance
“…The main idea behind these investigations is to reveal the further potential of the combined gel preparation to combat periodontal disease in closer than clinical situations. This was the outlook investigated in the studies published by [ 40 , 41 ]. The authors evaluated the efficiency of a green tea Catechin gel as an adjunct on human periodontal therapy.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The main idea behind these investigations is to reveal the further potential of the combined gel preparation to combat periodontal disease in closer than clinical situations. This was the outlook investigated in the studies published by [ 40 , 41 ]. The authors evaluated the efficiency of a green tea Catechin gel as an adjunct on human periodontal therapy.…”
Section: Resultsmentioning
confidence: 80%
“…In first work [ 40 ], the authors observed a significant reduction on pockets and inflammation during the 4 weeks of the clinical trial. In the second work [ 41 ], it was demonstrated that when used as an adjunct to periodontal treatment, green tea gel could provide benefit in reducing bleeding on probing and gingival inflammation at 1st and 3rd months of evaluation. What makes these studies even more relevant is the fact that the findings on complementary products for the treatment of human periodontitis still can be enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many studies have shown the potential treatment effects of catechins on periodontitis in vitro and in vivo . Recently, locally delivered green tea extract gel has been used as an adjunct to nonsurgical periodontal treatment . However, few studies have shown the potential effects of TFs in the control of periodontal disease, and these studies were limited to in vitro experiments .…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Recently, locally delivered green tea extract gel has been used as an adjunct to nonsurgical periodontal treatment. 30 However, few studies have shown the potential effects of TFs in the control of periodontal disease, and these studies were limited to in vitro experiments. 27 Thus, both the in vivo effects of TFs on individual inflammatory responses and the possibility for clinical application are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo realizou a administração da EGCG via gavagem em camundongos após a indução experimental da doença periodontal e observou-se que houve uma inibição de TNF, IL-6 e diminuição do número e atividade dos osteoclastos reduzindo, assim, a perda óssea alveolar (Cho et al, 2013). Estudos clínicos em humanos foram realizados utilizando-se uma formulação de tiras do extrato do chá (Kudva et al, 2011;Gadagi et al, 2013) ou em formulações à base de gel (Rattanasuwan et al, 2014) colocadas subgengivalmente após o procedimento de raspagem e polimento radicular. Em todos esses estudos houve uma melhora significativa da condição óssea e periodontal em comparação ao grupo controle.…”
Section: Introductionunclassified